Navigating Digital Transformation in Pakistan: A Discourse Analysis of the Media Representation of the Digital Pakistan Initiative. - Li, Zhou (Asian Studies Review, 2025)
This article explores how media narratives in Pakistan, specifically through Dawn and the News International, engaged with and reshaped discourse surrounding the Digital Pakistan initiative, which the Pakistan Tehreek-e-Insaf government launched in 2019. Guided by Laclau and Mouffe's discourse theory, the article identifies and explores two key themes in the media coverage: a shift in the Pakistani media's perspectives from initial optimism about digital inclusivity to concerns over the digital divide, and the challenges related to governance, stakeholder tensions, and civil liberties. By moving beyond a technological focus, the analysis reveals how media discourse reflects and contests the socio-political realities of the Pakistani government's initiative on digital transformation. The article highlights the need for a context-specific approach to digital policy that addresses deep-seated socioeconomic inequalities, stakeholder collaboration, and the safeguarding of civil liberties. It thereby contributes to discourse on digital transformation by emphasising the role of the media in shaping national projects and broadening the scope of media studies in developing countries.